AI-enabled 6G networks and applications - Gupta, Deepak; Ragab, Mahmoud; Mansour, Romany Fouad; Khamparia, Aditya 1988-; Khanna, Ashish (John Wiley & Sons, Inc., 2023)
"This book includes review of AI techniques for 6G Networks and will focus on deployment of AI techniques to efficiently and effectively optimize the network performance, including AI-empowered mobile edge computing, intelligent mobility and handover management, and smart spectrum management. This book also includes the design of a set of evolutionary AI hybrid algorithms with communication protocols, showing how to use them in practice to solve problems relating to vehicular networks, aerial networks and communication networks. It is intended as a reference guide to advanced hybrid computational intelligence methods for 6G supportive networks and protocols for graduate students and researchers in network forensics and optimization, computer science, and engineering. The chapters have been written and edited by active researchers, which cover hypotheses and practical considerations; provide insights into the design of evolutionary AI algorithms for 6G networks with focuses on network transparency, interpretability and simulatability for vehicular networks, space systems, surveillance systems and their usages in different emerging engineering fields."--
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on December 22, 2022)
Keywords: Mobile communication systems; Artificial intelligence; Radiocommunications mobiles; Intelligence artificielle; artificial intelligence